Pneumatosis intestinalis in a preterm infant: should we treat all intestinal pneumatosis as necrotising enterocolitis?. (28th March 2018) - Chew, Siu Jun; Victor, Rajadurai Samuel; Gopagondanahalli, Krishna Revanna; Chandran, Suresh
Abstract : Gastric pneumatosisis a very rare site of pneumatosis intestinalis (PI), and we report this finding in a preterm female infant with cyanotic congenital heart disease. The infant was stable initially on nasal intermittent mandatory ventilation; however, torrential pulmonary flow through a large patent ductus arteriosus prompted closure using oral ibuprofen. After an episode of haematochezia, she developed PI, affecting mainly the gastric wall and small intestine with portal venous gas. Her bowel movements were regular, with no abdominal distension or significant gastric aspirates. She was haemodynamically stable with negative infective markers. Management consisted of endotracheal intubation and ventilation, gastric decompression and broad-spectrum antibiotics. Both the gastric and intestinal pneumatosis resolved within 24 hours and she made an uneventful recovery. If PI is not due to necrotising enterocolitis, enteral nutrition can be initiated early and prolonged course of broad-spectrum antibiotics could have been avoided.